QUALITY CONTROL OF REGULAR SLOTTED CONTAINERS PRODUCTION PROCESS USING FAILURE MODE AND EFFECT ANALYSIS AND FAULT TREE ANALYSIS - Sugarindra, Muchamad; Tyas, Sekar Wijayaning; Parkhan, Ali; Fauza, Erlangga (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Quality control is an effort to ensure that the products produced meet the specified standards. The regular slotted containers (RSC) produced by PT. XYZ carry a high risk of defects during the production process, which can decrease product quality and company profitability. This study aims to evaluate the conformity of the production process with quality standards and to identify the root causes of defects and their improvement priorities. The methods used are Fault Tree Analysis (FTA) to systematically identify the root causes of defects, and Failure Mode and Effect Analysis (FMEA) to assess risk levels and develop improvement recommendations. The results revealed 38 types of defects, with delamination as the most dominant defect, caused by improper glue gap settings. Contributing factors include a lack of machine automation, fluctuations in raw material humidity, and inadequate glue gap inspections. The FMEA analysis showed that failures due to glue gap issues had the highest Risk Priority Number (RPN), which was 240, making it the top priority for improvement efforts. Recommended corrective actions include the implementation of automatic sensors, operator training, control of raw material humidity, and standardization of production parameters. The combined use of FTA and FMEA has proven to be effective in addressing quality issues in the company.PENGENDALIAN KUALITAS PROSES PRODUKSI REGULAR SLOTTED CONTAINERS MENGGUNAKAN FAILURE MODE AND EFFECT ANALYSIS DAN FAULT TREE ANALYSISPengendalian kualitas merupakan upaya untuk memastikan bahwa produk yang dihasilkan memenuhi spesifikasi yang telah ditetapkan. Produk regular slotted containers (RSC) pada PT. XYZ memiliki risiko cacat yang tinggi selama proses produksi, yang dapat menurunkan kualitas dan profitabilitas perusahaan. Penelitian ini bertujuan untuk mengevaluasi kesesuaian proses produksi dengan standar mutu yang ditetapkan serta mengidentifikasi akar penyebab cacat dan prioritas perbaikannya. Metode yang digunakan adalah Fault Tree Analysis (FTA) untuk menemukan akar penyebab cacat secara sistematis, serta Failure Mode and Effect Analysis (FMEA) untuk menilai tingkat risiko dan menyusun rekomendasi perbaikan. Hasil penelitian menunjukkan terdapat 38 jenis cacat, dengan delaminasi sebagai cacat dominan yang disebabkan oleh pengaturan glue gap yang tidak sesuai standar. Faktor penyebabnya antara lain kurangnya sistem otomatisasi, fluktuasi kelembapan bahan baku, dan inspeksi glue gap yang tidak berkelanjutan. Analisis FMEA menunjukkan bahwa kegagalan akibat glue gap memiliki nilai Risk Priority Number (RPN) tertinggi, yaitu 240, sehingga menjadi prioritas utama dalam upaya perbaikan. Penerapan sensor otomatis, pelatihan operator, pengendalian kelembapan bahan baku, dan standarisasi parameter produksi sebagai langkah perbaikan untuk mengatasi permasalahan terpilih. Penerapan FTA dan FMEA terbukti efektif menyelesaikan permasalahan kualitas pada perusahaan.